Postbiotics in oncology: science or science fiction? - Kudra, Anna; Kaźmierczak-Siedlecka, Karolina; Sobocki, Bartosz Kamil; Muszyński, Damian; Połom, Joanna; Carbone, Ludovico; Marano, Luigi; Roviello, Franco; Kalinowski, Leszek; Stachowska, Ewa (Frontiers in Microbiology, 2023)
The gut microbiome has been increasingly understood to play a critical role in carcinogenesis and cancer disease progression. The most recent research advancements have shown that different tools of microbiota manipulation contribute to gut microbiome-immune-oncology axis modulation, offering exciting opportunities for targeted interventions aimed at improving the efficacy of established anti-cancer therapy. Postbiotics are a new entry among the biotics showing beneficial effects on human health, while not requiring living cells to obtain the health effect and therefore not subject to food safety rules for live micro-organisms. Postbiotics are recently defined as “preparation of inanimate micro-organisms and/or their components that confers a health benefit on the host” and have gradually become the focus of scientific community. Since the beginning of research on this topic, numerous studies about postbiotics have been proved to strength the gut barrier, reduce inflammation, and promote antimicrobial activity. Anyway, research into the potential application to cancer therapy is still at the early stages of its efforts to uncover all the secrets surrounding postbiotics. This review aims to increase our understanding of the anti-cancer effect of postbiotics throughout a “bibliographic journey” on the biological activity of their components, including exopolysaccharides, cell wall fragments, tryptophan metabolites, enzymes, bacterial lysates, extracellular vesicles as well as short chain fatty acids, highlighting their perspective as new supportive therapeutic method of treatment and identifying the literature gaps where further research is needed.